Q-Switched Erbium-Doped Fiber Laser Using Cadmium Selenide Coated onto Side-Polished D-Shape Fiber as Saturable Absorber - Rusdi, Muhammad Farid Mohd; Mahyuddin, Mohamad Badrol Hisyam; Latiff, Anas Abdul; Ahmad, Harith; Harun, Sulaiman Wadi (IOP Publishing, 2018)
A stable Q-switched erbium doped fiber laser emitting at 1558nm is demonstrated using a cadmium selenide (CdSe) material coated onto a side-polished D-shape fiber as the saturable absorber (SA). By elevating the input pump power from the threshold of 91mW to the maximum available power of 136mW, a pulse train with a maximum repetition rate of 57.44 kHz, minimum pulse width of 3.76 μs, maximum average output power of 7.99mW, maximum pulse energy of 0.1391 μJ, and maximum peak power of 36.99mW are obtained. The signalto-noise ratio of the spectrum is measured to be around 75 dB. This CdSe based SA is simple, robust, and reliable, and thus suitable for making a portable pulse laser source.